Fe(II)/Et(3)N-Relay-catalyzed domino reaction of isoxazoles with imidazolium salts in the synthesis of methyl 4-imidazolylpyrrole-2-carboxylates, its ylide and betaine derivatives - Galenko, Ekaterina E (Beilstein J Org Chem, 2015)
A simple approach was developed for the synthesis of methyl 4-imidazolylpyrrole-2-carboxylates from easily available compounds, 5-methoxyisoxazoles and phenacylimidazolium salts under hybrid Fe(II)/Et(3)N relay catalysis. The products were easily transformed into the corresponding 3-(5-methoxycarbonyl-1H-imidazol-3-ium-3-yl)pyrrol-1-ides, which in turn can be hydrolyzed under basic conditions into the corresponding betaines. A carbene tautomeric form of the 4-methoxycarbonyl-substituted imidazolylpyrrolides was trapped by reaction with sulfur affording the corresponding imidazolethiones under very mild conditions.